Effect of maternal oxytocin on umbilical venous and arterial blood flows during physiological-based cord clamping in preterm lambs. - Fiona J Stenning (Public Library of Science (PLoS), 2021)
Background Delayed umbilical cord clamping (UCC) after birth is thought to cause placental to infant blood transfusion, but the mechanisms are unknown. It has been suggested that uterine contractions force blood out of the placenta and into the infant during delayed cord clamping. We have investigated the effect of uterine contractions, induced by maternal oxytocin administration, on umbilical artery (UA) and venous (UV) blood flows before and after ventilation onset to determine whether uterine contractions cause placental transfusion in preterm lambs. Methods and findings At ~128 days of gestation, UA and UV blood flows, pulmonary arterial blood flow (PBF) and carotid arterial (CA) pressures and blood flows were measured in three groups of fetal sheep during delayed UCC; maternal oxytocin following mifepristone, mifepristone alone, and saline controls. Each successive uterine contraction significantly (p<0.05) decreased UV (26.2±6.0 to 14.1±4.5 mL.min-1.kg-1) and UA (41.2±6.3 to 20.7 ± 4.0 mL.min-1.kg-1) flows and increased CA pressure and flow (47.1±3.4 to 52.8±3.5 mmHg and 29.4±2.6 to 37.3±3.4 mL.min-1.kg-1). These flows and pressures were partially restored between contractions, but did not return to pre-oxytocin administration levels. Ventilation onset during DCC increased the effects of uterine contractions on UA and UV flows, with retrograde UA flow (away from the placenta) commonly occurring during diastole. Conclusions We found no evidence that amplification of uterine contractions with oxytocin increase placental transfusion during DCC. Instead they decreased both UA and UV flow and caused a net loss of blood from the lamb. Uterine contractions did, however, have significant cardiovascular effects and reduced systemic and cerebral oxygenation.